2011
DOI: 10.3892/ijo.2011.923
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the forkhead transcription factor FOXL2 correlates with good prognosis in breast cancer patients treated with tamoxifen

Abstract: Abstract.Aromatase is an important enzyme in the local synthesis of oestrogens and its expression has been shown to be increased in breast cancer through the activation of multiple promoters. However, the mechanisms behind this are not yet fully understood. A novel candidate in this context is the transcription factor forkhead box L2 (FOXL2), which has been recognised to be co-expressed with aromatase and transcriptionally active promoter II in developing goat and chicken ovaries. We propose that FOXL2 could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…In order to find suitable models to test our vaccine, we screened several tumor cell lines, and in line with FOXL2 expression restriction in female organs, we found only modest levels of Foxl2 cDNA in 2 ovarian cancer cell lines (BR5 and ID8) and 1 breast cancer cell line (4T1). The latter observation is in agreement with a study by Wegman et al, who demonstrated that FOXL2 is expressed in some breast cancer patients ( 21 ). Because of the very low endogenous level of Foxl2 , we decided to overexpress the mutated form of Foxl2 to generate BR5-FOXL2 and 4T1-FOXL2 cell lines.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In order to find suitable models to test our vaccine, we screened several tumor cell lines, and in line with FOXL2 expression restriction in female organs, we found only modest levels of Foxl2 cDNA in 2 ovarian cancer cell lines (BR5 and ID8) and 1 breast cancer cell line (4T1). The latter observation is in agreement with a study by Wegman et al, who demonstrated that FOXL2 is expressed in some breast cancer patients ( 21 ). Because of the very low endogenous level of Foxl2 , we decided to overexpress the mutated form of Foxl2 to generate BR5-FOXL2 and 4T1-FOXL2 cell lines.…”
Section: Discussionsupporting
confidence: 93%
“…Due to the lack of any suitable GCT model ( 36 ) to test in vivo vaccine’s efficacy, we attempted to identify FOXL2 expression in several tumor cell lines. In line with a FOXL2 expression pattern in human female tissues ( 18 , 21 ), we found a very limited level of Foxl2 cDNA in 2 ovarian cancer cell lines (BR5 and ID8) and 1 breast cancer cell line (4T1) ( Supplemental Figure 6 ). The lack of Foxl2 expression prompted us to overexpress mutated Foxl2 C389G in BR5 and 4T1 cancer cell lines using a pCMV6-A-PURO vector ( Supplemental Figure 4A , right panel).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…In mammalian species, new reproductive tissues appeared, including the uterus, placenta and mammary gland. Collectively, our data as well as GEO profiles, NextProt-Beta data and the human protein atlas have documented the expression of FOXL2 in every female reproductive tissue: the oviduct, uterus (endometrium and myometrium), mammary gland and placenta [52,[54][55][56]63,73,88]. Interestingly, whereas FOXL2 is expressed in each reproductive tissue of mammalian female, its regulation varies with the nature of the reproductive tissue.…”
Section: Discussionmentioning
confidence: 57%